2023
DOI: 10.1038/s41598-023-29010-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI approaches for investigating microstructural complexity in a rat model of traumatic brain injury

Abstract: Our study explores the potential of conventional and advanced diffusion MRI techniques including diffusion tensor imaging (DTI), and single-shell 3-tissue constrained spherical deconvolution (SS3T-CSD) to investigate complex microstructural changes following severe traumatic brain injury in rats at a chronic phase. Rat brains after sham-operation or lateral fluid percussion (LFP) injury were scanned ex vivo in a 9.4 T scanner. Our region-of-interest-based approach of tensor-, and SS3T-CSD derived fixel-, 3-tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
(145 reference statements)
3
2
1
Order By: Relevance
“…Values were harmonized across sites to investigate longitudinal changes to the ipsilateral and contralateral CC following TBI-an interhemispheric fiber bundle particularly vulnerable to injury, 52 including following lateral FPI. 11,12,29,48,[53][54][55][56] We found that TBI was associated with reduced FA in both the ipsilateral and contralateral CC, consistent with previous findings 11,26,47,48,56,57 and likely reflecting a loss of myelinated axons. 9,47,55 Consistent with this, we also observed a significant effect of injury on ipsilateral CC susceptibility values, with increased susceptibility in the ipsilateral CC at 28 days after injury likely reflecting decreased myelin content.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Values were harmonized across sites to investigate longitudinal changes to the ipsilateral and contralateral CC following TBI-an interhemispheric fiber bundle particularly vulnerable to injury, 52 including following lateral FPI. 11,12,29,48,[53][54][55][56] We found that TBI was associated with reduced FA in both the ipsilateral and contralateral CC, consistent with previous findings 11,26,47,48,56,57 and likely reflecting a loss of myelinated axons. 9,47,55 Consistent with this, we also observed a significant effect of injury on ipsilateral CC susceptibility values, with increased susceptibility in the ipsilateral CC at 28 days after injury likely reflecting decreased myelin content.…”
Section: Discussionsupporting
confidence: 91%
“…11,12,29,48,[53][54][55][56] We found that TBI was associated with reduced FA in both the ipsilateral and contralateral CC, consistent with previous findings 11,26,47,48,56,57 and likely reflecting a loss of myelinated axons. 9,47,55 Consistent with this, we also observed a significant effect of injury on ipsilateral CC susceptibility values, with increased susceptibility in the ipsilateral CC at 28 days after injury likely reflecting decreased myelin content. 9 In the ipsilateral CC, changes in ADC depended on the time after injury.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other investigations also showed that white matter atrophy was associated with elevated MD and reduced FA 46 . Consistent with the findings of Chary and colleagues 56 , the ic in TBI rats during the chronic phase exhibited a decrease in FA, a decrease in AD, an increase in RD, and an increase in MD, which can be attributed to microstructural changes, such as the loss of myelinated axons and/or the accumulation of iron deposits. However, their findings in the CCs region partially align with our results, showing a decrease in FA, an increase in RD, and an increase in MD.…”
Section: Discussionsupporting
confidence: 88%
“…It is often assumed that lower fractional anisotropy values may correspond to a reduction of the white matter microstructural integrity. 71 However, emerging evidence suggests that higher fractional anisotropy and axial diffusivity values can be attributed to factors such as cytotoxic edema during the acute phase following injury 72 , 73 , 74 as well as glial scarring and a manifestation of recovery and/or compensation in the chronic phase, 69 , 72 , 74 , 75 , 76 or simply in the voxels with less fiber crossings. In these conditions, the interpretation of higher fractional anisotropy values as solely indicative of increased white matter integrity may not hold true.…”
Section: Discussionmentioning
confidence: 99%